2013
DOI: 10.4028/www.scientific.net/amr.662.823
|View full text |Cite
|
Sign up to set email alerts
|

Levitation Control of a Planar Magnetic Levitation Stage Based on Improved Auto-Disturbance Rejection Controller

Abstract: In the present study, we proposed a magnetic levitation positioning stage for the high-precision positioning and scanning tasks in micro-electronics manufacturing and precision machining. This stage consists of a thrust system and a levitation system, the latter is a strong-coupling and nonlinear MIMO system related closely to both levitation height of each terminal magnetic bearing and instantaneous plane location of the movers and is focused on in our study. The dynamic model of this levitation system is so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Zhou et al . confirmed that this type of non‐smooth characteristic could easily cause a chattering phenomenon in a system's response. Therefore, in order to avoid this undesired chattering, a new nonlinear function, which was defined by nfal ( e ′( k ), c , b , γ ) , was adopted to replace fal ( e ′( k ), a , δ ) : {italicnfal(),,,e()kcbγ=b0.25emarctanc()e()kγμ0π/2μ0μ0=arctan()c()0γ …”
Section: Positioning Controller Designmentioning
confidence: 76%
“…Zhou et al . confirmed that this type of non‐smooth characteristic could easily cause a chattering phenomenon in a system's response. Therefore, in order to avoid this undesired chattering, a new nonlinear function, which was defined by nfal ( e ′( k ), c , b , γ ) , was adopted to replace fal ( e ′( k ), a , δ ) : {italicnfal(),,,e()kcbγ=b0.25emarctanc()e()kγμ0π/2μ0μ0=arctan()c()0γ …”
Section: Positioning Controller Designmentioning
confidence: 76%
“…It has been pointed out and proven by Zhou et al [26][27][28] that such unsmooth characteristics may easily cause the chatter phenomenon of system responses. Therefore, a new nonlinear function for replacing the fal(e 0 (k), a, d) is defined in this study as nfal(e 0 (k), c, b, g) 27,28…”
Section: Esomentioning
confidence: 99%
“…When equation (22) is used to process the estimation, the nonlinear function fal(e 0 (k), a, d) is adopted with the following characteristics: in case of small deviation, the gain will be large; while in case of large deviation, the gain will be small. It has been pointed out and proven by Zhou et al [26][27][28] that such unsmooth characteristics may easily cause the chatter phenomenon of system responses. Therefore, a new nonlinear function for replacing the fal(e 0 (k), a, d) is defined in this study as…”
Section: Positioning Controllermentioning
confidence: 99%